2021
DOI: 10.1097/md.0000000000024377
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal papillary adenocarcinoma harboring a fusion of ROS1 with GOPC

Abstract: Rationale: Nasopharyngeal papillary adenocarcinoma is a region-specific tumor originating from the nasopharyngeal surface epithelium. Owing to its rarity, more attention has been paid to its clinicopathologic features, while little effort has been made to study the gene abnormalities that drive this tumor. We describe the first case of nasopharyngeal papillary adenocarcinoma harboring a fusion of ROS1 with GOPC. Patient concerns: A 22-year-old female pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Although the tumor is histomorphologically very similar to thyriod papillary carcinoma (TPC) and expresses TTF-1, it can be clearly differentiated from TPC immunohistochemically by being thyroglobulin and Napsin-A negative. [1,3,4,6] Our cases showed strong TTF-1 and CK7 expression, and in addition, Case 2 also showed focal S100, p63, and p40 expression. Although thyroglobulin is almost…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Although the tumor is histomorphologically very similar to thyriod papillary carcinoma (TPC) and expresses TTF-1, it can be clearly differentiated from TPC immunohistochemically by being thyroglobulin and Napsin-A negative. [1,3,4,6] Our cases showed strong TTF-1 and CK7 expression, and in addition, Case 2 also showed focal S100, p63, and p40 expression. Although thyroglobulin is almost…”
Section: Discussionmentioning
confidence: 53%
“…[8] In addition to the positivity of TTF-1, the negativity of CK20 and CDX2 distinguishes it from intestinal-type adenocarcinoma. [6,7] The molecular genetic studies showed no mutation in the BRAF and KIT gene, RT-PCR and FISH assays were negative for SYT-SSX1/2 fusion transcripts and SYT (18q11.2) gene rearrangement. [1,3] Similar to the examples in the literature.…”
Section: Peer-reviewmentioning
confidence: 99%
See 3 more Smart Citations